Description of City Population Growth Rate of Banda Aceh Post Tsunami 24 December 2014 - Muhammad Okta Ridha Maulidian; Hasmunir Hasmunir (Proceedings of AICS - Social Sciences, 2017)
Banda Aceh City is an experienced area with Tsunami in 2004, by the history more than half of its territory was under threat of the tsunami. This research aims to calculate how population growth rates in Banda Aceh post-tsunami 2004 as the prone area? The study examines population data of Banda Aceh descriptively. Collections in this research are documented, on secondary data from the BPS (Central of Statistical Officer) Banda Aceh. The results show that highest population occurred in 2013 was 262223 inhabitants. Population growth rate in Banda Aceh City post-tsunami 2004 increased and decreased in tandem, but at the end of annual, population growth rate was the minus: -23,2 (exponential) or -2,5 (geometry). However, if observed by sub-districts, the highest population growth rates are in tsunami-prone areas, Meuraxa and Kuta Raja where the rates were 21,48 (exponential) or 23,9 (geometry), and 14,63 (exponential) or 15,76 (geometry). This was very high rate, the growth of ordinary residents only on lift 2 - 4 percent per year